The economic triangulation Beijing-Yerevan-New Delhi: Cooperation or competition? - Orazio Maria Gnerre (Banber Arevelagitut'yan Instituti, 2025)
Since it is no longer part of the Soviet Union, Armenia has found itself in the position of being able to choose its partners independently. This was largely determined by proximity relations, by historical ones with Russia, and by the places where the emigration of Armenia’s own people took place. Beyond that, it is placed in conditions of choice between cooperation with some actors rather than others. In this sense, Armenia has started dialogue and trade relations with two Asian giants, China and India. The article proposes to recap the relations between these countries, paying attention to the factors that could allow a triangular cooperation rather than a competition.